2015
DOI: 10.1378/chest.14-0041
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease in People With Idiopathic Pulmonary Fibrosis

Abstract: Rationale & ObjectivePeople with idiopathic pulmonary fibrosis (IPF) have been shown to be at an increased risk of cardiovascular disease but reasons for this are unknown. The aim of this study was to compare the prevalence of common cardiovascular risk factors in people with IPF and the general population and establish the incidence of ischaemic heart disease (IHD) and stroke after the diagnosis of IPF, controlling for these risk factors. MethodsWe used data from a large United Kingdom primary care database t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 26 publications
4
49
1
2
Order By: Relevance
“…Pulmonary hypertension and obstructive sleep apnea are frequent comorbidities of IPF, and a link between CKD and these conditions has been reported [31,32] . Additionally, recent epidemiologic studies have revealed that patients with IPF had an increased risk of hypertension, diabetes mellitus, and cardiovascular disease [7,14,18,19] , all of which are closely associated with CKD. Moreover, there may be mechanistic links between CKD and IPF, such as cellular senescence and oxidative stress [33,34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary hypertension and obstructive sleep apnea are frequent comorbidities of IPF, and a link between CKD and these conditions has been reported [31,32] . Additionally, recent epidemiologic studies have revealed that patients with IPF had an increased risk of hypertension, diabetes mellitus, and cardiovascular disease [7,14,18,19] , all of which are closely associated with CKD. Moreover, there may be mechanistic links between CKD and IPF, such as cellular senescence and oxidative stress [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…IPF has risk factors for CKD similar to COPD, such as old age and smoking. Moreover, recent studies have reported that patients with IPF have an increased risk of hypertension, diabetes mellitus, and cardiovascular disease, and that these comorbid conditions may be associated with increased mortality [14,18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…A validated COPD code list34 was the basis of our COPD code list (see online supplement for additional codes). The code lists used to identify patients with bronchiectasis12 and ILD35 are published.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the rate of first-time CAD events was significantly higher in the patients with IPF than in the control subjects (RR: 2.32); however, the incidence of stroke was only marginally higher for IPF. A high prevalence of coronary risk factors in IPF did not fully account for the increased risk of CAD, suggesting that IPF itself was a specific risk factor for CAD 40) .…”
Section: -4 Vascular Events In Patients With Interstitial Pneumoniamentioning
confidence: 93%